Influence of Specimen Size on Autogenous Volume Deformation of Long-Aged MgO-Admixed Concrete - Chen, Changli; Chen, Rongfei; Zhao, Zhenhua; Li, Weiwei; Yan, Shaolian; Du, Xiangqin; Yang, Huashan (Frontiers in Materials, 2021)
The transformation law of autogenous volume deformation of MgO-admixed concrete with specimen size was revealed through continuous observation on standard-size (Φ200 mm × 500 mm), medium-size (Φ250 mm × 500 mm), and large-size specimens (Φ250 mm × 600 mm) over 6 years. Besides, the pore parameters of concrete core samples obtained from autogenous volume deformation specimens in the 1st, 3rd, and 6th years of age were investigated. The results show that the autogenous volume deformation of MgO-admixed concrete increases with the increase in the MgO content or age. The expansion rate of the concrete specimen decreases after the age of 360 days, and the autogenous volume expansion deformation of the specimen tends to be stable after about 2 years. When the size of the specimen changes, the autogenous volume deformation of MgO-admixed concrete decreases with the increase of specimen size. During the age of 2–6 years, the expansion of medium- and large-size specimens is reduced by 6–10 and 15–20%, respectively, compared with the standard-size specimens under the same MgO content. With the condition of an appropriate MgO content, regardless of the size of the specimen, the pore structure of the concrete becomes better and better with the growth of age, the concrete becomes denser and denser, and the expansion caused by MgO hydration will not cause damage to concrete structures.